2013
DOI: 10.1111/apa.12421
|View full text |Cite
|
Sign up to set email alerts
|

EXPRESS study shows significant regional differences in 1‐year outcome of extremely preterm infants in Sweden

Abstract: AimThe aim of this study was to investigate differences in mortality up to 1 year of age in extremely preterm infants (before 27 weeks) born in seven Swedish healthcare regions.MethodsNational prospective observational study of consecutively born, extremely preterm infants in Sweden 2004–2007. Mortality was compared between regions. Crude and adjusted odds ratios and 95% CI were calculated.ResultsAmong 844 foetuses alive at mother's admission for delivery, regional differences were identified in perinatal mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 32 publications
7
64
1
3
Order By: Relevance
“…When infant characteristics were added into the risk adjustment model, the variation in overall stillbirth and in-hospital mortality rates across the study regions reduced by nearly onequarter (23.3%), indicating the lack 7 Investigation of the effect of adjusting for maternal, pregnancy, and infant characteristics by the timing of death shows that interregional variation persists at all 3 specified timings. This is contrary to the findings of the EXPRESS study in Sweden, 11 which concluded that in the most extreme preterm infants, any regional differences were established <12 hours after birth, suggesting they could be related to variations in immediate perinatal practices. The continued wide variation in mortality for infants ≥12 hours of age in the EPICE cohort could indicate that there is variation in the quality, access, and provision of neonatal care across Europe.…”
Section: Figurecontrasting
confidence: 99%
“…When infant characteristics were added into the risk adjustment model, the variation in overall stillbirth and in-hospital mortality rates across the study regions reduced by nearly onequarter (23.3%), indicating the lack 7 Investigation of the effect of adjusting for maternal, pregnancy, and infant characteristics by the timing of death shows that interregional variation persists at all 3 specified timings. This is contrary to the findings of the EXPRESS study in Sweden, 11 which concluded that in the most extreme preterm infants, any regional differences were established <12 hours after birth, suggesting they could be related to variations in immediate perinatal practices. The continued wide variation in mortality for infants ≥12 hours of age in the EPICE cohort could indicate that there is variation in the quality, access, and provision of neonatal care across Europe.…”
Section: Figurecontrasting
confidence: 99%
“…Survival at the lowest gestational ages (23–24 weeks) varies in population-based reports, primarily as different countries and hospitals assume contrasting stances as to the provision of active care (figure 1). Data from the USA most vividly demonstrate this variation;1 survival is highest in situations where more active obstetric and neonatal management is practised 2. Interpreting survival without knowing the proportion of live births for whom active stabilisation was given is impossible and reports need to be explicit with regard to this.…”
Section: Survival and Neonatal Outcomesmentioning
confidence: 99%
“…Among the improvements are the widespread application of antenatal glucocorticoid therapy, the introduction of synthetic surfactant, and a tendency towards more aggressive feeding strategies, although regional differences in the treatment of VP and VLBW infants do exist [13]. Therefore, the entities VP and VLBW can only be compared between populations that have received the same care.…”
Section: Introductionmentioning
confidence: 99%